STUNTING IN ISLAMIC FAMILY LAW: CAUSE DAN SOLUTION - Moh Rosil Fathony (Universitas Islam Indonesia, 2023)
This article discusses the causes and solutions of stunting and its effect on household harmony. In addition, this article also discusses the government's efforts in overcoming health problems as Perpres Number. 72/2021 concerning the Acceleration of Stunting Reduction. The method that used in this article is descriptive qualitative which is library research. Article data in the form of literature data, especially books and equipped with other documents that related to stunting both causes and solutions. The results of the article show that stunting is a condition that a person's height is shorter than the height of other people in general (who are the same age). Stunting is a chronic nutritional problem caused by multi-factorial and intergenerational nature. Stunting is also something that is not expected to happen in a household, in Indonesia stunting is a health problem that must be taken seriously. However, in practice, stunting still occurs a lot and is a problem today. Widespread incidence of stunting hampers economic growth, increases poverty, and widens inequality in households.